A robust high-speed sliding mode control of permanent magnet synchronous motor based on simplified hysteresis current comparison - Ifeanyi Chinaeke-Ogbuka; Augustine Ajibo; Kenneth Odo; Uche Ogbuefi; Muncho Mbunwe; Cosmas Ogbuka; Emenike Ejiogu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
A robust high-speed sliding mode control (SMC) of three phase permanent magnet synchronous motor (PMSM) is presented. The SMC served for inner speed control while a simplified hysteresis current control (HCC) scheme was used in the outer current control to generate gating signals for the inverter switches. The present research leverages on the ability of SMC to directly access system speed error which it attempts driving to zero by cancelling modelling uncertainties and disturbances. Performance comparison was done for the SMC model and an existing model having classical PI controller. With the initial positive speed command of 200 rpm at 5 Nm constant loading, rotor speed with SMC neatly settled to the reference speed at 0.085 seconds without overshoot while the rotor speed of the model with PI controller settled at 0.217 seconds after overshoot. This translates to 155.3% speed enhancement. Similar superior speed performance of the SMC was also observed during recovering from sudden speed reversal. While the SMC model recovered and settled to the reference speed of -200 rpm at 0.369 seconds, the model with PI controller settled at 0.482 seconds. From the results, it can be seen that SMC demonstared superiority over the conventioanl PI controller for complex drives systems.